Susceptibility of rodents to Stellantchasmus falcatus infection - Saenphet S. (2014)
Two rodent hosts, rats (Rattus norvegicus) and mice (Mus musculus), were examined for their susceptibility to Stellantchasmus falcatus infection. The metacercariae were recovered from half-beaked fish, Dermogenus pusillus, collected from Hang Dong District, Chiang Mai Province. A single inoculation of three hundred metacercariae was orally conducted with male rats (n=15) and mice (n=15). Uninfected animals were used as controls (n=5). At days 3, 7, 14, 21 and 28, post-infection (PI), three rats and mice, also one from each control group, were sacrificed for adult worm recovery, and the blood was drawn by heart puncture and prepared for white blood cell and eosinophil counts. The results showed that adult worm recovery gradually decreased after day 21 PI in the rats, whereas, reduction in the mice was found after day 7 PI and the adult worms completely disappeared at day 28 PI. Hematologically, total white blood cell counts in two kinds of infected hosts were not statistically different from those of controls. However, eosinophil counts of infected rats slightly increased during days 7-14 PI, and started to decrease at day 21 PI. A similar finding was observed in the infected mice. From these results, it can be concluded that the rat is a more suitable host for S. falcatus than the mouse. To understand the mechanisms implicated in determining host susceptibility, intensive studies are required.